Ethnobotanical Knowledge of Khandadevi and Gokulganga Rural Municipality of Ramechhap District of Nepal - Pradhan, Suman Prakash; Chaudhary, Ram Prasad; Sigdel, Sagar; Pandey, Bishnu Prasad (Ethnobotany Research and Applications, 2020)
Background: This study was focused on the ethnobotany of different ethnic communities residing in Majhuwa and Chuchure villages of Khandadevi and Gokulganga Rural Municipality of Ramechhap District of Bagmati Province of the Federal Democratic Republic of Nepal. Methods: The ethnobotanical study was carried out by using semi-structured questionnaires in which participatory rural appraisal (PRA) and rapid rural appraisal (RRA) tools were used to acquire knowledge from local people regarding ethnobotanical uses of plants of their surroundings. The quantitative data were analyzed by the relative frequency of citation (RFC), use value (UV), and informant consensus factor (ICF). Results: A total of 139 plant species belonging to 74 families were found to have ethnobotanical significance. Among these species, herbs accounted for 41% followed by trees (29%), shrubs (14%), climbers (9%), grasses (3%), epiphytes (1%), ferns (1%), fungi (1%), and lichens (1%). Out of which, 136 species were of medicinal importance and used to treat different ailments followed by other uses such as fodder, veterinary, religious, pesticide, timber, etc. The new uses of Lespisorus mehrae, Plumbago zeylanica, Pterocarpus santalinus, Rhus parviflora, and Roscoea auriculata were found. The highest RFC was found to be 0.82 for Ageratina adenophora, Curcuma domestica, Acorus calamus, Centella asiatica, Avena sativa, and Allium sativum. The highest UV was found in Zingiber officinale (1.30), and the highest ICF was found in the gastro-intestinal disorders ailment category (0.50). Conclusions: For the first time, we revealed the ethnobotanical application of plant species from Majhuwa and Chuchure villages of Ramechhap District. This study showed that Majhuwa and Chuchure villages are rich in medicinally important plant species and different ethnic communities have enormous knowledge of ethnobotanical uses of plants. Moreover, illegal collection, trade, and marketing have threatened the abundance and distribution of some high-value medicinal plants. It is of utmost importance to conserve floral diversity through the local peoples’ participation. Key Words: Ramechhap, Medicinal Plants, Ethnobotanical knowledge, UV, RFC, ICF